Changes provoked by altitudes and cooking methods in physicochemical properties, volatile profile, and sensory characteristics of yak meat - Xijin Zhu; Chao Yang; Yu Song; Yu Qiang; Dong Han; Chunhui Zhang (Food Chemistry: X, 2023)
The present study aimed to shed light on the effects of altitudes and three cooking methods (boiling, steaming, and roasting) on the physicochemical quality, volatile profile, and sensorial characteristics of yak meat. Composite meat samples were prepared to represent each cooking method and altitude level from the longissimus thoracis et lumborum (LTL) muscle of nine yaks. The techniques employed were gas chromatography-mass spectrometry (GC–MS) and electronic nose (E-nose) along with chemometrics analysis to study the changes occurring in yak volatile profile, and TBARS measurement in lipid oxidation during cooking. Among the cooking methods, boiling and steaming exhibited higher protein and fat content while lower volatile compound contents. Additionally, roasted yak meat received the highest sensory scores, along with decreased L*-values, while elevated a*- and b*-values, and tenderness. A total of 138 volatile compounds were detected, and among them, 36 odorants were identified as odor-active compounds in cooked yak meat. It is evidenced that low-altitude yak presented more complex and richer flavor profiles than high-altitude ones. Moreover, yak meat from low- and high-altitude was classified into two groups by an electronic nose (E-nose) owing to distinct flavor characteristics. Overall, roasted yak meat originating from low altitudes tends to be more popular from a sensory perspective.